2012
DOI: 10.1002/etc.1984
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nanopolystyrene on the feeding behavior of the blue mussel (Mytilus edulis L.)

Abstract: As the industrial production of nanoplastic and the degradation of microplastic into smaller particles at sea increase, the potential amount of nanoplastics in the marine environment rises. It has been reported that mussels uptake 100-nm polystyrene (PS) beads; to date, however, the effects of this uptake on the organism are unknown. In the present study, the authors investigated the effects of 30-nm PS on the feeding behavior of the blue mussel (Mytilus edulis) by exposing the organism to different nano PS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
214
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 496 publications
(236 citation statements)
references
References 70 publications
14
214
2
6
Order By: Relevance
“…Wegner et al 51 found the mussel, M. edulis, reduced feeding rates in the presence of plastics, and hypothesised that the mussels were able to detect the microplastic and alter their feeding behaviour. Juvenile and adult sea urchins are known to selectively feed on seaweeds and artificial diets that are highly palatable and/or nutritious 52,53 .…”
Section: Discussionmentioning
confidence: 99%
“…Wegner et al 51 found the mussel, M. edulis, reduced feeding rates in the presence of plastics, and hypothesised that the mussels were able to detect the microplastic and alter their feeding behaviour. Juvenile and adult sea urchins are known to selectively feed on seaweeds and artificial diets that are highly palatable and/or nutritious 52,53 .…”
Section: Discussionmentioning
confidence: 99%
“…Shim et al (2014) used SEM-EDS to confirm the presence of nanoplastics in abrasion experiments. In their effect study with mussels (Mytilus edulis), Wegner et al (2012) used multiple wavelength UV-VIS as a proxy to detect pink-dyed nanoparticles and used dynamic light scattering (DLS) to track the actual size of the bioavailable aggregates over time. Velzeboer et al (2014a) used transmission EM and conventional light microscopy to characterise pristine nanopolystyrene particles and aggregates, respectively.…”
Section: Detection and Occurrence Of Nanoplasticmentioning
confidence: 99%
“…This trade-off has not yet been quantified for NPs. Wegner et al (2012) were the first to measure and model the homoaggregation of 30 nm polystyrene particles in seawater and found rapid formation of 1000 nm aggregates within 16 minutes. Attachment efficiencies of 1 were required to explain the experimental observations (Wegner et al 2012).…”
Section: Fate Of Nanoplasticmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purpose, mussel (Mytilus sp.) was taken as a biological model, since these organisms are one of the most surveyed targets for addressing ingestion and potential effects of microplastics, due to being filter-feeding bivalves (Browne et al 2008;Farrell and Nelson 2013;Van Cauwenberghe et al 2015;Wegner et al 2012). …”
Section: Introductionmentioning
confidence: 99%